Molecular insight into reproductive toxicity and transgenerational effects of Cadmium exposure on Drosophila melanogaster - Yi Pan; Ke Fan; Linhao Zong; Yantao Luo; Xin Ni; Dong Chen; Jinjun Qian; Fei Ma; Jie Cheng; Miao Guan (Ecotoxicology and Environmental Safety)
Cadmium (Cd), a widespread and serious environmental pollutant, has recently garnered increasing scientific scrutiny due to its profound adverse effects. Although the evidence for Cd-induced reproductive toxicity is well established, it remains elusive on the intricate dose-response relationship and underlying molecular mechanisms, especially for transgenerational toxicity in animals. Here, we employed fruit fly (Drosophila melanogaster) as a model organism to examine the reproductive performance across five generations by parental exposure to varying concentrations of Cd (5, 50, and 500 μM). Firstly, our observations on the number of eggs laid, pupae formed, and adult flies emerged on the directly exposed generation (F0) confirmed a dose-dependent decline in fecundity. Transcriptome analysis revealed that, Cd-induced oxidative stress and ion transport disruption in the F0 generation could underlie synaptic dysfunction and impaired follicle cell development, impacting reproductive behavior and oocyte fertility. Employing dose-response analysis, Wnt signaling pathway and mTOR signaling pathway were identified as early molecular responses to Cd-induced toxicity. Secondly, sustained detrimental effects were observed for at least two to three generations after Cd removal. At the epigenetic level, Cd could perturb fecundity across generations by modulating Dnmt2 expression, a pivotal regulator of methylation processes. Moreover, despite phenotypic recovery in F4, persistent molecular changes indicate enduring toxicity, highlighting the need for vigilance against environmental Cd contamination and its long-term effects. Collectively, our findings enhance the understanding of Cd-induced reproductive toxicity and its transgenerational effects, and highlight the need to further improve the assessment of the multigenerational consequences of environmental Cd contamination.